Pentingnya Penerapan Etika Bisnis pada Perdagangan Secara Elektronik di Indonesia - Setiawan, Rasyid; Setiadi, Muhammad Hari; Afrizaldi, Afrizaldi (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2023)
Electronic commerce is one of the proofs of technological advances that have made people more creative in the business world. In keeping up with the progress and sophistication of technology that brings many positive values, you still have to pay attention to ethics in business when carrying out buying and selling activities in electronic commerce. This study aims to determine the importance of applying business ethics to electronic commerce in Indonesia. The method used by researchers is a descriptive qualitative method. The data sources used by researchers are literature studies and literature to find out the importance of applying business ethics to electronic commerce in Indonesia. The results show that ethics in business is something that must be carried out in commerce, the application of business ethics such as store service friendliness in responding to each customer and the goods sent according to the pictures of the goods in E-Commerce advertisements greatly affect customer satisfaction in transactions in E-Commerce. This shows that in every transaction on E-Commerce it is necessary to have good business ethics in traders.